2020
DOI: 10.1016/j.arrct.2020.100068
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vibration Therapy on Walking Endurance in Children and Young People With Cerebral Palsy: Do Age and Gross Motor Function Classification System Matter?

Abstract: Objective To investigate the effect of age and Gross Motor Function Classification System (GMFCS) level on walking endurance after 20 weeks of vibration therapy in children and young people with cerebral palsy (CP). Design The study was a clinical trial without control group comparing baseline and postintervention outcomes within participants. Setting Vibration therapy was performed at school or at home. Assessments took place in a clinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
2
7
0
1
Order By: Relevance
“…The 6MWT was used in other types of intervention, such as games and virtual reality activities, orthoses and whole-body vibration [ 7 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The use of internet-based intervention or intensive short-duration virtual reality intervention for 4 to 20 weeks reported significant improvements in the 6MWT when the children were involved in gross motor activity games.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The 6MWT was used in other types of intervention, such as games and virtual reality activities, orthoses and whole-body vibration [ 7 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The use of internet-based intervention or intensive short-duration virtual reality intervention for 4 to 20 weeks reported significant improvements in the 6MWT when the children were involved in gross motor activity games.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 124 studies were initially identified; after a review of the full text, 87 were excluded, as they included neurodegenerative or genetic disorders ( n = 55), as they were case reports ( n = 15), or as they did not provide details on 6MWT ( n = 17). The remaining 37 articles [ 7 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], comprising a total of 1292 children, met the inclusion criteria after a review of the full text ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Motor skills development is generally connected with obesity in children, especially the gross motor skills (C Graf, 2004) that happens due to the energy intake higher than energy expenditure (Soetjingsih, 2014) and seldom performing physical activities, (Ramdani & Azizah, 2020) involving big muscles (Papalia & Feldman, 2015) like running, jumping, climbing, kicking, whereas physical activities are important factors supporting the development of academic skills of young child ( Ali et al, 2017). Other problems connected with the development of children's' gross motor skills as found by (Nisnayeni, 2012); (Telford, et al 2020), are delays on children's development like delay to stand up, less able to swing hands, and cannot follow the rhythmic gymnastic well, and as it is also influential on the development of motor skills, children face problems in reading (Overvliet, et al, 2011), and children age 5-6 years seem lazy to move their body especially arms and legs (Fuaidah, & Miftahillah, 2018). The development of children's motor is still dominated by boys (Bardid, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%